2018
DOI: 10.1091/mbc.e18-05-0305
|View full text |Cite
|
Sign up to set email alerts
|

The tetraspanin CD82 regulates bone marrow homing and engraftment of hematopoietic stem and progenitor cells

Abstract: Hematopoietic stem and progenitor cell (HSPC) transplantation represents a treatment option for patients with malignant and nonmalignant hematological diseases. Initial steps in transplantation involve the bone marrow homing and engraftment of peripheral blood-injected HSPCs. In recent work, we identified the tetraspanin CD82 as a potential regulator of HSPC homing to the bone marrow, although its mechanism remains unclear. In the present study, using a CD82 knockout (CD82KO) mouse model, we determined that CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…In CD82 knockout mice, HSPCs from the knockout exhibited stem cell migratory and spreading defects. This was found to be related to hyeractivation of Rac 1 GTPases in these CD82 knockout HSPCs since Rac1 inhibition rescued homing capacity 51 …”
Section: Hspc Homing: Rolling Adhesion and Transmigrationmentioning
confidence: 91%
“…In CD82 knockout mice, HSPCs from the knockout exhibited stem cell migratory and spreading defects. This was found to be related to hyeractivation of Rac 1 GTPases in these CD82 knockout HSPCs since Rac1 inhibition rescued homing capacity 51 …”
Section: Hspc Homing: Rolling Adhesion and Transmigrationmentioning
confidence: 91%
“…Similarly, a previous study focused on CD151 identified interactions with integrins β1 and αIIbβ3 as critical for promoting HSPC adhesion to various ECMs ( Fitter et al, 1999 ) and both CD81 and CD82 were shown to mediate α4β1 adhesion of erythroblasts to Vascular Cell Adhesion molecule-1 ( Spring et al, 2013 ). More recently, our work using the CD82KO mouse model identified a homing and engraftment defect of HSPCs, which was linked to altered Rac1 activity ( Saito-Reis et al, 2018 ), further illustrating that CD82 may serve as a therapeutic target to modulate HSPC adhesion and migration.…”
Section: Tetraspanins: Hsc Adhesion Migration and Signaling Within mentioning
confidence: 83%
“…A number of tetraspanin knock out (KO) mice have been generated, but up until now, only two have displayed an HSC defect. CD82KO animals exhibit a reduction in LT-HSCs, resulting from increased stem cell activation and reduced quiescence signaling ( Hur et al, 2016 ; Saito-Reis et al, 2018 ). In contrast, HSCs from CD81KO mice appear to proliferate similarly to control animals, but demonstrate a reduced ability to reenter quiescence after stimulation ( Lin et al, 2011 ).…”
Section: Tetraspanins: Hsc Quiescencementioning
confidence: 99%
“…The tetraspanin CD82 was also found to be upregulated in several leukemias, including AML ( 16 ), with aberrant CD82 expression detected specifically in chemotherapy-resistant CD34 + /CD38 − AML cells ( 17 , 18 ). Additionally, work from our group identified CD82 as a key regulator of AML cell homing to the bone marrow ( 19 ) and demonstrated that CD82 modulates the spatial and temporal dynamics of Protein Kinase C α (PKCα) signaling in AML ( 20 ).…”
Section: Introductionmentioning
confidence: 99%